Reimagining the future of African brain health: Perspectives for basic research on the pathogenesis of cryptococcal meningitis - R. Dangarembizi (Elsevier, 2021)
Cryptococcal meningitis is a fatal opportunistic infection of the brain and a leading cause of neurological damage and death in immunocompromised individuals. This neglected fungal disease of the brain is a huge burden on the health systems of developing countries, especially in Sub-Saharan Africa, where up to 25% of people living with HIV/AIDS succumb to it. Cryptococcal fungal cells have a predilection for the brain and they are capable of traversing the blood brain barrier and invade the brain where they cause infection, inflammation and a disruption of normal brain function. A robust host neuroimmune response is critical for pathogen clearance and survival, and a good understanding of the mechanisms underlying its development in the host is critical for the development of effective treatments. However, past basic research studies have been focussed on the characteristics of the fungus and its effect on the peripheral immune system; with little attention paid to how it interacts with brain immune cells. This mini review briefly discusses the paucity of basic research data on the neuroimmune response to cryptococcal infection, raises pertinent questions on how the brain cells respond to the fungal infection, and thereafter discusses models, techniques and advanced technologies that could be useful for carrying out high-throughput research on the pathogenesis of cryptococcal meningitis.